STRATEGI GURU PAI DALAM MENINGKATKAN PEMAHAMAN SISWA PADA PELAJARAN SKI DI MTS MIFTAHUL ULUM TAMBAKASRI KECAMATAN SUMBERMANJING WETAN KABUPATEN MALANG - Ayu Ismania; Anwar Sa’dullah; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The learning strategy in the subject of Islamic Cultural History is an effort to apply thevalues of Islamic cultural teachings that are able to be practiced by students in reallife. Because strategy plays an important role in the learning process in order toachieve learning objectives. Researchers chose this location because MTs. MiftahulUlum Tambakasri Sumbermanjing Wetan Malang Regency to find out the teacher'sstrategy in improving students' understanding of SKI lessons. This research is aqualitative research. Data was collected by observation, interviews, anddocumentation. As for the data analysis, the author uses a qualitative descriptiveanalysis, which is in the form of a written presentation of data regarding related data,both written and verbal, from the object of research at the institution mentionedabove, which has been observed, where in this case the author describes thoroughlyabout the real situation. The results showed that students' understanding of SKIlessons at MTs. Miftahul Ulum Tambakasri showed good results, using expository,inquiry, and cooperative learning strategies, using lecture, question and answer,discussion, and assignment methods